Fabrication and dielectric properties of lead titanate nanocomposites - R. Wongmaneerung (2018)
A simple powder mixing and pressure-less sintering process for fabrication of PbTiO3(PT) nanocomposites (micron-sized PT matrix reinforced with either PT nanoparticles or nanofibers) has been developed to enhance both densification and dielectric properties. The potentiality of a ceramic-nanocomposite technique as a low-cost and simple ceramic fabrication to obtain highly dense and pure PT/PT composites was demonstrated. It has been found that both densification and dielectric properties of the composites fabricated in this work were significantly enhanced, as compared to the two-stage sintering and the conventional PT ceramics. © 2008 Elsevier B.V. All rights reserved.